2012
DOI: 10.1093/nar/gks1056
|View full text |Cite
|
Sign up to set email alerts
|

Rrp5p, Noc1p and Noc2p form a protein module which is part of early large ribosomal subunit precursors in S. cerevisiae

Abstract: Eukaryotic ribosome biogenesis requires more than 150 auxiliary proteins, which transiently interact with pre-ribosomal particles. Previous studies suggest that several of these biogenesis factors function together as modules. Using a heterologous expression system, we show that the large ribosomal subunit (LSU) biogenesis factor Noc1p of Saccharomyces cerevisiae can simultaneously interact with the LSU biogenesis factor Noc2p and Rrp5p, a factor required for biogenesis of the large and the small ribosomal sub… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
82
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 65 publications
(100 citation statements)
references
References 88 publications
16
82
0
2
Order By: Relevance
“…We found that many pre-60S subunit assembly factors were enriched in Nog2-containing particles when Drs1 was depleted, especially early assembly factors such as Ssf1, Npa1, and Rrp5, all of which have been reported to dissociate from pre-ribosomes before 27SB pre-rRNA is generated and before Nog2 binds pre-ribosomes in wild-type cells (Fig. 3A,D,E ;Fatica et al 2002;Nissan et al 2002;Dez et al 2004;Hierlmeier et al 2012).…”
Section: Resultsmentioning
confidence: 83%
See 4 more Smart Citations
“…We found that many pre-60S subunit assembly factors were enriched in Nog2-containing particles when Drs1 was depleted, especially early assembly factors such as Ssf1, Npa1, and Rrp5, all of which have been reported to dissociate from pre-ribosomes before 27SB pre-rRNA is generated and before Nog2 binds pre-ribosomes in wild-type cells (Fig. 3A,D,E ;Fatica et al 2002;Nissan et al 2002;Dez et al 2004;Hierlmeier et al 2012).…”
Section: Resultsmentioning
confidence: 83%
“…However, recent studies, including this one (Fig. 1), have shown that 23S pre-rRNA is likely an alternative, on-pathway intermediate to mature 18S rRNA Adams et al 2002;Miles et al 2005;Hierlmeier et al 2012;Jakovljevic et al 2012;Talkish et al 2014). Depletion of Drs1, like many pre-60S subunit assembly factors that function during processing of 27S pre-rRNA, results in a dramatic decrease in 20S pre-rRNA with a corresponding increase in 35S and 23S pre-rRNA levels (Fig.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations